Reappraisal of Fresnosaurus drescheri (Plesiosauria; Elasmosauridae) from the Maastrichtian Moreno Formation, California, USA. (31st December 2016) - O'Gorman, José P.
Abstract: The elasmosaurid Fresnosaurus drescheri, Welles from the contact between the Tierra Loma/Marca members of the Moreno Formation (Maastrichtian), California, USA is reviewed. Most of the features included in Welles's original diagnosis are considered related only to the juvenile ontogenetic stage of the holotype and only specimen. The new diagnosis is based on diagnostic characters of the ilia, including long rectangular shaped sacral facets located in the dorsal part of the shaft, two gentle knobs in the shafts and unexpanded dorsal end. Additional material from the Moreno Formation (numbered under the same number as the F . drescheri holotype but not mentioned by Welles and therefore considered part of a different specimen) are described for the first time. The latter are referred to the aristonectine, being the first evidence of aristonectines from the North Hemisphere.